Dari Krisis ke Stabilitas: Menganalisis Perjalanan Pemulihan Keuangan BPD - Mutmainah; Muhammad Meidy Nur Hafidz (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study aims to analyze the development of net profit in Bank Pembangunan Daerah (BPD) in Indonesia during the period from 2020 to 2024. The research problem focuses on the significant fluctuation in net profit observed in BPD, particularly after the impact of the COVID-19 pandemic. This descriptive quantitative study analyzes financial reports and secondary data from the Financial Services Authority (OJK) and Bank Indonesia. The findings indicate that BPD experienced a significant decline in net profit in 2020, followed by a steady recovery in the subsequent years. Key factors such as improved credit risk management, government stimulus policies, and increased non-interest income contribute to this recovery. The novelty of this research lies in its focus on the post-pandemic financial dynamics of BPD, which has not been widely explored in previous studies. The findings contribute to a deeper understanding of the factors influencing BPD’s financial performance, providing recommendations for future strategic improvements in financial management. Keywords: Regional Development Bank; Net Profit; COVID-19 Impact; Financial Recovery; Risk Management